Relación entre el estrés y adherencia al tratamiento en pacientes con diabetes tipo 2 en el Centro de Salud N°3 - Jiménez Mosquera, Sara Noemí (2020)
Mellitus diabetes is a chronic disease with a high rate of poor adherence to treatment, influenced by emotional factors such as stress, which increase morbidity and mortality due to complications that impact quality of life and cause socio-economic damage, so it is important to know if there is a relationship between stress and treatment adherence in the local population in order to improve therapeutic effectiveness. The objectives of present investigation were: to determine the stress level presented by patients with diabetes type 2, to determine adherence to pharmacological and non-pharmacological treatment, and to identify the association between stress and adherence to treatment in patients with diabetes. The study was descriptive, prospective, with a quantitative approach in 140 patients with diabetes type 2 seen at the Loja Health Center No. 3. The Stress test was used; Morisky-Green test; IMD-Chile test and a questionnaire about exercise and alcohol consumption. Getting the following results: 40% (n=56) presented moderate stress; 64.3% (n=90) did not comply with the pharmacological treatment; 65.7% (n=92) showed moderate adherence to mediterranean diet; 70.7% (n=99) low adherence to exercise and 98.7% (n=138) low alcohol consumption. The stress level presented a significant association with poor adherence to pharmacological treatment (p=0.000) and exercise (p=0.001). In conclusion, the stress is associated with poor adherence to pharmacological treatment and physical exercise; however, it was not associated with adherence to diet. Key words: Pharmacological adherence, diet, exercise